Improved Sensitivity of SPR Instrument Using Multiple Reflection Technique - Rajavelan, M; Gnanavel, C; Baldwin Immanuel, T; Muthukumar, P (International Journal of Engineering and Technology, 2018)
Surface Plasmon Resonance Instrument plays a vital role in the field of bio technology, bio medical and Pharmaceutical applications.Â However, the SPR instrument is still used and promoted because it is the only important tool for biological applications. As the instrument has shown its utility in the field of biological investigations including protein studies, many research laboratories are installing the instrument for their studies. The technique is supposed to be a â€˜label-freeâ€™ method which is an added advantage compared to extensive analytical methods.Â With all these attributes, if only the instrument could be a bit more economical and affordable in running costs,Â its usefulness would have pervaded into even routine observations such as in pollution monitoring, foodstuff examination and other contamination studies in many biological and drug testing applications. The gold coated glass slide is vanished for usage of few samples and this has to be prevented. For preventing the gold washing a lacquer coating is introduced and this gives a multiple dips. The multiple reflections occur is summed through PIC microcontroller and display in the LCD screen of instrument. The multiple reflections are more sensitive than the conventional SPR technique. This paper describes the multiple reflection sensitivity and improved sensitivity of the SPR instrument.Â Â